Development of Store-Operated Calcium Entry-Targeted Compounds in Cancer - Liang, Xiaojing; Zhang, Ningxia; Pan, Hongming; Xie, Jiansheng; Han, Weidong (Frontiers in Pharmacology, 2021)
Store‐operated Ca2+ entry (SOCE) is the major pathway of Ca2+ entry in mammalian cells, and regulates a variety of cellular functions including proliferation, motility, apoptosis and death. Accumulating evidence has indicated that augmented SOCE is related to the generation and development of cancer, including tumor formation, proliferation, angiogenesis, metastasis and antitumor immunity. Therefore, the development of compounds targeting SOCE has been proposed as a potential and effective strategy for use in cancer therapy. In this review, we summarize the current research on SOCE inhibitors and blockers, discuss their effects and possible mechanisms of action in cancer therapy, and induce a new perspective on the treatment of cancer.